CORRELATION BETWEEN LIVER FUNCTIONAL PARAMETERS AND DISORDERS OF PORTOLIVER CIRCULATION OF BLOOD AND LYMPHOKINESIS IN CHILDREN WITH CIRRHOSIS - A.A. Gafurov; V.V. Botvin'eva; M.M. Aliev (Вопросы современной педиатрии)
.